Representation Of Trauma In Mandela’s Speech “no Easy Walk To Freedom” - Bekkai , Selma; Daoudi, Frid (El Omda in Linguistics and Discourse Analysis, 2023)
At the time of his death on December 5th, 2013, Nelson Mandela was a well-known political and social leader on an international scale. In recent years, historical trauma has emerged as a concept to describe the effects of Black colonization, cultural suppression, and historical oppression. The scope of this study encompasses fields as diverse as history, literature, trauma studies, linguistics and psychology. This research paper attempts to investigate the trauma ideology inherent in Mandela's speech “No Easy Walk to Freedom”. Therefore, the main research questions are: How is trauma communicated in Mandela's speech? Moreover, how is trauma transmitted by critical discourse analysis strategies? The paper draws upon Mandela's presidential address No Easy Walk to Freedom to the ANC (Transvaal) Congress on September 21st, 1953 in Transvaal, South Africa.